Bio-derived 3D TiO2 hollow spheres with a mesocrystal nanostructure to achieve improved electrochemical performance of Na-ion batteries in ether-based electrolytes. Issue 7 (29th January 2019) - Yang, Rongrong; Sun, Lanju; Liu, Wei; Zhang, Yuan; Cui, Yongpeng; Du, Yongxiu; Liu, Shuang; Wang, Huanlei; Huang, Minghua
Abstract : Novel hollow TiO2 spheres with mesocrystal shells were fabricated via sacrificial bio-templates, exhibiting enhanced Na + ion storage in ether-based electrolyte. Abstract : On the way to pursue advanced energy storage cells, an ingenious design and exquisite structure of electrode materials are key to success. In this work, we rationally prepared a unique mesocrystal TiO2 hollow sphere with a mesoporous shell by employing sulfonated-squid ink as templates. This is the first mesocrystal example with a hollow and porous sphere-like scaffold, which contributes to the synthetic coupling effect of SO x 2− species and unique marine bio-templates. The specific combination of the 3D hierarchical porous architecture and mesocrystal nature not only offers large surface areas and rich porosity for the transfer of Na-ions during the electrochemical process, but also improves electronic conductivity and structural integrity owing to the little lattice mismatch of mesocrystals. As anode materials for sodium ion batteries, the obtained mesocrystal hollow TiO2 spheres exhibited a higher initial coulombic efficiency and sodium storage capacity (143 mA h g −1 at 2 A g −1 ), better rate performance and cycling stability (110 mA h g −1 after 1000 cycles at 1 A g −1 ) in an ether-based electrolyte than in an ester-based one, demonstrating a good match between the electrode materials and ether-based electrolyte. Therefore, these findings could open a new gate for rationally preparing new electrode materials for Na-ion batteries in new electrolyte systems.